2018
DOI: 10.1039/c8fo00685g
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine restriction regulated energy and protein homeostasis by improving thyroid function in high fat diet mice

Abstract: Methionine-restricted diets (MRD) show an integrated series of beneficial health effects, including improving insulin sensitivity, limiting fat deposition, and decreasing oxidative stress, and inflammation responses. We aimed to explore the systemic responses to a MRD in mice fed with a high fat (HFD) and clarify the possible mechanism. Mice were fed with a control diet (0.86% methionine + 4% fat, CON), HFD (0.86% methionine + 20% fat), or MRD (0.17% methionine + 20% fat) for 22 consecutive weeks. HFD-fed mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 62 publications
3
31
0
1
Order By: Relevance
“…Arachidonic acid, an unsaturated fatty acid, is positively related to pro-inflammatory cytokines, but inversely correlated with Akkermansia and exacerbates non-alcoholic steatohepatitis (NASH) by promoting the growth of pro-inflammatory bacteria, enhancing the inflammatory response, reducing the abundance of butyrate-producing bacteria, and inducing insulin resistance [34], [35]. A high-fat diet can induce thyroid dysfunction in rodent models, and that the thyroid volume is significantly increased in obese individuals, in contrast to healthy ones [36], [37]. Here, the enrichment scores for Arachidonic acid metabolism and Thyroid hormone synthesis were restored to relatively lower levels after the inulin-supplemented diet.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid, an unsaturated fatty acid, is positively related to pro-inflammatory cytokines, but inversely correlated with Akkermansia and exacerbates non-alcoholic steatohepatitis (NASH) by promoting the growth of pro-inflammatory bacteria, enhancing the inflammatory response, reducing the abundance of butyrate-producing bacteria, and inducing insulin resistance [34], [35]. A high-fat diet can induce thyroid dysfunction in rodent models, and that the thyroid volume is significantly increased in obese individuals, in contrast to healthy ones [36], [37]. Here, the enrichment scores for Arachidonic acid metabolism and Thyroid hormone synthesis were restored to relatively lower levels after the inulin-supplemented diet.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al. () found that methionine‐restricted diets improved metabolic disorders induced by high fat diet (HFD) in mice. In contrast with this, Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…After a 7‐day acclimatization period, C57BL/6J mice were randomly assigned into two groups: the control group fed with the normal diet (CON, n = 30; 0.86% methionine + 4% fat; mainly based on the AIN‐76A formulation, 73%, 17%, and 10% of calories from carbohydrate, protein, and fat, respectively; energy density 3.8 kcal g −1 ; Collaborative Medicine Bioengineering Co., Ltd. Jiangsu, China) or a high‐fat diet group fed with the high fat diet ( n = 90; 0.86% methionine + 24% fat; 41%, 14%, and 45% of calories from carbohydrate, protein, and fat, respectively; energy density 4.7 kcal g −1 ; Collaborative Medicine Bioengineering Co., Ltd. Jiangsu, China) . After 10 weeks of high‐fat diet treatment, given the possibility of the obesity‐resistant mice according to previous reports, 60 heavier mice were numbered and selected as DIO mice.…”
Section: Additional Experimental Sectionmentioning
confidence: 99%
“…Their body weights were significantly higher than those of the control group (41.14 ± 0.62 g vs 30.23 ± 0.41 g, p < 0.01). DIO mice were then divided into two groups: the high fat diet group still fed with the high‐fat diet (HF, n = 30, DIO mice) and the high‐fat + methionine‐restricted diet group fed with the high‐fat and 80%‐methionine‐restricted diet (HF + MR, n = 30, DIO mice; 0.17% methionine + 24% fat; 41%, 14%, and 45% of calories from carbohydrate, protein, and fat, respectively; energy density 4.7 kcal g −1 ; Collaborative Medicine Bioengineering Co., Ltd. Jiangsu, China), respectively . The compositions of three experimental diets are listed (Table S1, Supporting Information).…”
Section: Additional Experimental Sectionmentioning
confidence: 99%